Influence of receptor selectivity on benefits from SGLT2 inhibitors in patients with heart failure: a systematic review and head-to-head comparative efficacy network meta-analysis - Täger, Tobias; Frankenstein, Lutz; Atar, Dan; Agewall, Stefan; Frey, Norbert; Grundtvig, Morten; Clark, Andrew L.; Cleland, John G. F.; Fröhlich, Hanna (Clinical research in cardiology, 2022)
Background  Receptor selectivity of sodium-glucose cotransporter-2 inhibitors (SGLT2i) varies greatly between agents. The overall improvement of cardiovascular (CV) outcomes in heart failure (HF) patients varies between trials. We, therefore, evaluated the comparative efficacy of individual SGLT2i and the influence of their respective receptor selectivity thereon. - Methods  We identified randomized controlled trials investigating the use of SGLT2i in patients with HF—either as the target cohort or as a subgroup of it. Comparators included placebo or any other active treatment. The primary endpoint was the composite of hospitalization for HF or CV death. Secondary outcomes included all-cause mortality, CV mortality, hospitalization for HF, worsening renal function (RF), and the composite of worsening RF or CV death. Evidence was synthesized using network meta-analysis. In addition, the impact of receptor selectivity on outcomes was analysed using meta-regression. - Results  We identified 18,265 patients included in 22 trials. Compared to placebo, selective and non-selective SGLT2i improved fatal and non-fatal HF events. Head-to-head comparisons suggest superior efficacy with sotagliflozin as compared to dapagliflozin, empagliflozin or ertugliflozin. No significant difference was found between canagliflozin and sotagliflozin. Meta-regression analyses show a decreasing benefit on HF events with increasing receptor selectivity of SGLT2i. In contrast, receptor selectivity did not affect mortality and renal endpoints and no significant difference between individual SGLT2i was noted. - Conclusion  Our data point towards a class-effect of SGLT2i on mortality and renal outcomes. However, non-selective SGLT2i such as sotagliflozin may be superior to highly selective SGLT2i in terms of HF outcomes.